3D printing technology in the management of carpal tunnel syndrome: A case report (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
A 35-year-old individual with carpal tunnel syndrome presented with tingling and numbness in the left thumb, index, and middle finger. A 3D printed CTS splint was crafted to immobilize the affected wrist joint, aiding pharmacotherapy. At six weeks, evaluations included the Boston Carpal Tunnel Questionnaire (BCTQ), Visual Analogue Scale (VAS) for pain, and Evaluation of Satisfaction with assistive Technology (QUEST) version 2.0.9. Substantial improvements were observed in Bangla-BCTQ scores (symptom severity scale: 3.68 vs. 1.27; functional status scale: 2.74 vs. 1.31), VAS (70 vs. 30), and QUEST scores. 3D printing technology may contribute to better personalized musculoskeletal care enhancing quality of life.